THE EFFECT OF INFLATION ON THE PERFORMANCE OF SHARIA BANKS: PENGARUH INFLASI TERHADAP KINERJA PEMBIAYAAN BANK SYARIAH - Sari Lubis, Raya (LPPM UPMI, 2023)
This study aims to determine whether inflation affects the Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF). The method in this research is quantitative associative. The data used is secondary data which is publication data that has been collected by other parties. Sources of data for each variable were obtained from the official website of Badan Pusat Statistik (https:// bps.go.id), Bank Indonesia (https://www.bi.go.id) and Otoritas Jasa Keuangan (www.ojk. go.id). The results of this study indicate that inflation has a positive or negative effect on the Financing to Depocit Ratio (FDR) and Non Performing Financing (NPF). The point is that inflation has an influence on FDR and NPF. However, the effect varies greatly each period according to the IRF inflation response graph test to FDR, or the IRF inflation response graph to NPF. If it is related to each other, Inflation, Financing to Depot Ratio (FDR) and Non-Performing Financing (NPF) are said to have direct or indirect effects and impacts that are interrelated but not too large in the banking industry.